Case Report: Unmasking sustainable left ventricular recovery in chronic heart failure with axillary temporary mechanical circulatory support - Desai, Aarti; Sharma, Shriya; Luce, Caitlyn; Ruiz, Jose; Goswami, Rohan (Frontiers in Cardiovascular Medicine, 2024)
Background Mechanical circulatory support (MCS), temporary or durable, is essential in patients with acute heart failure presenting in cardiogenic shock (CS). MCS is fundamental in patients with advanced heart failure when used as a bridge to decision, transplant or left ventricular recovery. Limited data on acute-on-chronic heart failure (HF) patients exists in the era of axillary mechanical circulatory support with the Impella 5.5. We describe a case of chronic ischemic cardiomyopathy, HF-CS, in a patient who underwent Impella placement, medical optimization, and explant, now with sustained normalization in ejection fraction. Case summary A Caucasian female in her 50 s was referred to our center for evaluation for advanced therapies, including transplantation or durable left ventricular assist device placement. Her initial ejection fraction was 30% with comorbidities including multivessel coronary artery disease revascularized with 3 vessel bypass grafting ten years prior, type 2 diabetes (A1c 8.6%), and peripheral vascular disease. During her evaluation, she had acute decompensation leading to cardiogenic shock and required hospitalization with inotrope initiation, which was unable to be weaned. She was approved for organ transplant and listed; however, she required escalation of support and eventual placement of right axillary Impella 5.5. While on Impella support, her vasoactive needs reduced, and she was found to have left ventricular recovery and tolerated the initiation of guideline medical therapy. After three weeks of support, the Impella was weaned and explanted, and the patient was discharged. She remains stable with a sustained ejection fraction of greater than 50% with NYHA class 1 functional status at follow-up. One year later, the patient showed sustained myocardial recovery with guideline-directed medical therapy (GDMT). Conclusion Our case highlights a unique approach in patients with long-standing (>5 years) heart failure who may benefit from early consideration for axillary support and concomitant optimization with guideline-directed medical therapy to assess for explant and native heart recovery.